Welcome to Scribd. Sign in or start your free trial to enjoy unlimited e-books, audiobooks & documents.Find out more
Standard view
Full view
of .
0 of .
Results for:
P. 1
Mathematical Induction

# Mathematical Induction

Ratings: (0)|Views: 16|Likes:

### Availability:

See more
See less

07/13/2014

pdf

text

original

Mathematical Induction 1Running head: MATHEMATICAL INDUCTIONPROOF BY MATHEMATICAL INDUCTIONStephen SchouppWestern Governors University

Mathematical Induction 2Proof by Mathematical InductionA significant facet of mathematics is to detect and differentiatereoccurring designs or sequences. To define these designs or sequences,mathematicians implement the theorem of mathematical induction. Definedas a “method of proving statements concerning a positive integral variable”(Answers.com, 2008), induction seeks to establish the validity of any infinitesequence defined by a subset of natural numbers.Induction establishes the cogency of the sequences first affirmation,known as the base step, by establishing the validity of the sequence for
x
= 1.The next operation, the induction hypothesis, demonstrates the verity of astochastic succeeding statement such that the sequence holds true for
x
=
n.
Thus, by the inductive step, if the base step is true for
x
= 1 and theinduction hypothesis
x
=
n
is also true, then the infinite sequence is valid for any positive integer
x
=
n
+ 1 for n > = 1.To illustrate how induction works, a proof can be devised from asequence with arbitrary positive integer
n
having property such that the sumof the first
n
even numbers is equal to
n
(
n
+1). By letting
P
denote this property, we can write this relationship as function
P
(
n)
and that
P
(
n
) =
n
(
n+
1). For these functions to be true, we must validate the base step, the

induction hypothesis, and the inductive step.Mathematical Induction 3To prove our sequence, the sum of the first
n
even numbers is equal to
n
(
n
+1), by mathematical induction, we must first state our proposition (thatwhich is to be proved) in terms of property
P
, positive even integers
n,
ands the function of
P
(
n
) for n >=1:
P
(
n
) = 2+4+6...+2
n = n
(
n+
1):
n
> = 1 For this statement to be genuine, we must establish the cogency of the basestep, by letting
n
be the smallest possible case (remember
n
>=1) which inthis instance is 1 and substituting 1for
n
in our original function:
(
n
) = 2+4+6...+2
n = n
(
n+
1),if
n
= 1, then
P
(1) = 2(1)
=
1(1
+
1)
P
(1) = 2 = 1(2)
P
(1) = 2 = 2Hence,
P
(1) is true, and the base step is grounded.With the base step holding true, the original equation can be projected andassumed to be genuine in terms of a subsequent positive integer
n
such that:
P
(
n
) =
n
(
n+
1):
n
> = 1